Clinical Profile of Patients with Chronic Liver Disease - Tiwari, Pratap Sagar; Shah, Surendra; KC , Sudhamshu (Journal of Nobel Medical College, 2025)
Background: Chronic liver disease is a major problem worldwide. Understanding the demographics, clinical profile, and staging of the condition helps in forming a better management plan for the disease and which reflects the outcomes as well. Materials and Methods: Three hundred and eighty patients with chronic liver disease were prospectively studied at the Department of Hepatology in Nobel Medical college, which is a tertiary care hospital of eastern Nepal, from September 2023 to March 2024. Clinical characteristics, endoscopy results and lab reports were studied. Statistical Package for the Social Sciences (SPSS) version was used for the analysis. Results: Mean age was 48.3±11.1 years with 73 % males. The maximum number of patients [112 (29.5%)] belonged to the age group 45-54 years old. The aetiology of Chronic liver disease was alcohol-related in 81 %. Chronic Hepatitis B virus and Hepatitis C virus-related liver disease was found in 11.6% & 2.6 % of patients. Eighty-six percent had esophageal varices. There were 11.8% patients with MELD score <10, 35.5% with MELD score 10-15, and 52.6% with MELD score >15. Based on the Child-Pugh score, 15.5% of patients were in CPC-A, 38.4% were in CPC-B, and 46.1% were in CPC-C at presentation. Conclusion: Alcohol-related liver disease is the most common cause of Chronic liver disease in Nepal, followed by Chronic Hepatitis B and Hepatitis C virus-related liver disease. Most patients present in their advanced stages, as reflected by esophageal varices and high MELD & Child Pugh scores.